PEMBUATAN PROGRAM APLIKASI PENGGAJIAN KARYAWAN - Olivia Saraswati Tjipto; Dali S. Naga; Ririen Setyarini (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Designing employee’s payroll application program is an integrated payroll system. The purpose of this study is to design to solve problems which are found in manual payroll system which can slow down the system of company.The method that is used for designing system is System Development Life Cycle (SDLC) with waterfall approach. SDLC contains four phases: planning phase, analysis phase, design phase and implementation phase. The programming language which is used for making this system is PHP and the database which is used is PHP MySQL. The purpose of designing employee’s payroll application program is to provide the system’s work and reduce the mistakes in calculating the salary. Key wordsPHP, MySQL, Penggajian, SDLC